The Effect of Synovectomy in Total Knee Arthroplasty for Primary Osteoarthritis: A Meta-Analysis - Kooner, Sahil Singh; Clark, Marcia (The Journal of Knee Surgery, 2017)
The objective of this study is to assess pain, function, and morbidity in patients undergoing synovectomy during primary total knee arthroplasty (TKA) for osteoarthritis (OA). A meta-analysis, which included randomized controlled trials comparing TKA with and without synovectomy for OA, was completed. The primary outcome was postoperative knee pain. Secondary outcomes included performance, perioperative complications, validated functional scores, operation length, and hospitalization length. A literature search produced 487 unique references, of which 3 randomized controlled trials were selected for inclusion. A total of 304 patients (354 knees) were included, with an average age of 67 years. Follow-up intervals between studies ranged from 26 weeks to 12 months. Included studies were of moderate- to high-quality evidence with low risk of bias. There was no significant difference between the two groups in regard to postoperative pain, Knee Society Score, or postoperative range of motion. Postoperative blood loss was significantly lower in synovium-retaining TKA group (MD = 99.41 mL; 95% confidence interval, 45.08–153.75). Based on these results, there is currently no evidence to support the use of synovectomy in TKA for primary OA, as it provides no clinical benefit and increases postoperative blood loss.
Keywords: blood loss; total knee arthroplasty; synovectomy; osteoarthritis